Measurement of inclusive and differential cross sections of single top quark production in association with a W boson in proton-proton collisions at s $$ \sqrt{s} $$ = 13.6 TeV - The CMS collaboration; A. Hayrapetyan; A. Tumasyan; W. Adam; J. W. Andrejkovic; T. Bergauer; S. Chatterjee; K. Damanakis; M. Dragicevic; P. S. Hussain; M. Jeitler; N. Krammer; et al. (Journal of High Energy Physics)
Abstract The first measurement of the inclusive and normalised differential cross sections of single top quark production in association with a W boson in proton-proton collisions at a centre-of-mass energy of 13.6 TeV is presented. The data were recorded with the CMS detector at the LHC in 2022, and correspond to an integrated luminosity of 34.7 fb −1. The analysed events contain one muon and one electron in the final state. For the inclusive measurement, multivariate discriminants exploiting the kinematic properties of the events are used to separate the signal from the dominant top quark-antiquark production background. A cross section of 82.3 ± 2.1 stat − 9.7 + 9.9 syst ± 3.3 lumi $$ 82.3± 2.1{\left(stat\right)}_{-9.7}^{+9.9}\left(syst\right)± 3.3\left(lumi\right) $$ pb is obtained, consistent with the predictions of the standard model. A fiducial region is defined according to the detector acceptance to perform the differential measurements. The resulting differential distributions are unfolded to particle level and show good agreement with the predictions at next-to-leading order in perturbative quantum chromodynamics.